AlSi10Mg alloy and laser powder bed melting preparation method thereof
By introducing a new seed alloy into the AlSi10Mg alloy and using laser powder bed melting technology, the grain refinement and microstructure optimization of the alloy are achieved, solving the problem of poor mechanical properties of Al-Si-Mg alloy in laser powder bed melting, and significantly improving its strength and plasticity.
Patent Information
- Application Number
- CN202411737796.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-29
AI Technical Summary
In the prior art, Al-Si-Mg series alloys have poor mechanical properties during the melting of laser powder beds, and traditional high-strength aluminum alloys are prone to cracks at high temperatures, resulting in limited application.
A new seed alloy was introduced into the AlSi10Mg alloy, and mixed powders were prepared through laser powder bed melting technology to achieve grain refinement and microstructure optimization of the alloy.
The strength and plasticity of AlSi10Mg alloy were significantly improved, with a yield strength of 302±7.6MPa, a tensile strength of 479.2±1.5MPa, and an elongation of 11.1±0.7%, expanding its application in laser powder bed melting technology.
Smart Images

Figure CN119634748A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of alloy additive manufacturing, and in particular relates to an AlSi10Mg alloy and a laser powder bed melting preparation method thereof. Background Art
[0002] As the demand for manufacturing high-performance complex geometric components increases, laser powder bed melting, as a widely used metal additive manufacturing technology, has attracted more and more attention. However, the application of lightweight aluminum alloys in laser powder bed melting is still limited, especially in terms of improving mechanical properties. Current research on aluminum alloys mainly focuses on Al-Si-Mg series alloys, which generally have good processability but relatively poor mechanical properties. In addition, studies have widely verified that the high-temperature crack sensitivity of traditional high-strength aluminum alloys (such as 2xxx and 7xxx series forging alloys) during laser powder bed melting hinders their application. Although many studies have shown that elements such as Sc, Zr, Ti and Ta can be widely added in casting for nucleation, which may help crack suppression, grain refinement and performance improvement, these key raw materials should be avoided because they may lead to high costs and supply risks. Therefore, how to improve the mechanical properties of Al-Si-Mg alloys manufactured by laser powder bed melting so that they have excellent strength and plasticity at the same time is a problem to be solved by the present invention. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides an AlSi10Mg alloy and a laser powder bed melting preparation method thereof. The present invention introduces a new seed alloy into the AlSi10Mg alloy to achieve grain refinement and microstructure optimization of the AlSi10Mg alloy prepared by laser powder bed melting, thereby improving the strength and plasticity of the AlSi10Mg alloy.
[0004] The present invention is specifically implemented through the following technical solutions.
[0005] The present invention provides a laser powder bed melting preparation method of AlSi10Mg alloy, comprising the following steps:
[0006] The seed alloy powder and the AlSi10Mg alloy powder are uniformly mixed to prepare a mixed powder; the seed alloy powder consists of the following components: 0<Ti≤2.63wt%, 0<C≤0.66wt%, 0<B≤0.13wt%, and the remainder is Al, which is 100% in total; in the mixed powder, the mass fraction of the seed alloy powder is 15wt%.
[0007] The dried mixed powder is spread flat on the base plate of the forming chamber to form an alloy powder layer.
[0008] Under the protection of inert gas, the alloy powder layer is laser scanned and melted layer by layer to obtain AlSi10Mg alloy.
[0009] Preferably, the seed alloy powder is prepared by vacuum induction gas atomization process, the average particle size of the seed alloy powder is 9.62μm, and the seed alloy powder contains Ti(C, B) particles, and the particle size of the Ti(C, B) particles is 50nm to 300nm. It should be noted that the Ti(C, B) particles are formed by B atoms occupying the C vacancies of the TiC crystal. Because the Ti(C, B) phase is formed by B atoms occupying the C vacancies of the TiC crystal, the Ti(C, B) still retains the structure of the TiC crystal. It is completely different from the TiBC ternary phase, which is a ternary phase composed of Ti, B and C.
[0010] Preferably, the AlSi10Mg alloy powder is relatively spherical as a whole, and the average particle size of the AlSi10Mg alloy powder is 30 μm.
[0011] Preferably, during the forming process, the printing of each layer is first performed by the laser beam according to a preset scanning path to complete the solid forming of the internal area. After the forming of the internal area is completed, the laser beam scans and forms the external contour from the inside to the outside along the internal solid edge of the layer, and finally completes the single-layer printing; the steps of single-layer printing are repeated layer by layer until the additive manufacturing of the AlSi10Mg alloy is completed.
[0012] Preferably, during the forming process, the laser scanning path of each layer forms an angle of 67° with the laser scanning path of the previous layer.
[0013] Preferably, the laser process parameters used for printing internal entities and contours are: the laser power is set to 200W to 350W, the laser scanning speed is 600mm / s to 1800mm / s, the scanning interval is 0.1mm, and the powder layer thickness is 0.03mm.
[0014] Preferably, the composition of the AlSi10Mg alloy powder is: 0<Si≤9.8wt%, 0<Mg≤0.6wt%, and the content of Al is ≥89.6wt%, which is 100% in total.
[0015] Preferably, use commercial The AlSi10Mg alloy powder and the Al-2.63Ti-0.66C-0.13B seed alloy powder were uniformly mixed by a shaker mixer at a fixed oscillation frequency of 50 Hz for 100 minutes to ensure that the powders were fully fused to form TM-AlSi10Mg powder.
[0016] Preferably, the mixture is dried in a vacuum oven at 80° C. for 10 hours.
[0017] Preferably, printing is performed on a 6061 aluminum alloy platform, and flowing argon is used in the chamber to minimize oxygen contamination, which is controlled below 0.1 vol%. There is no need to preheat the printing platform in advance.
[0018] The present invention also provides an AlSi10Mg alloy prepared by the above preparation method, the average grain size of the AlSi10Mg alloy is 2.8μm, and the microstructure of the AlSi10Mg alloy is: a double-peak heterogeneous microstructure formed by the periodic arrangement of fine equiaxed crystals (melt pool boundary) and coarse equiaxed crystals (inside the melt pool).
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention introduces seed alloy powder into AlSi10Mg alloy powder for modification to prepare mixed powder, wherein the seed alloy powder consists of the following components: 0<Ti≤2.63wt%, 0<C≤0.66wt%, 0<B≤0.13wt%, and the remainder is Al, which is 100% in total. Then, the mixed powder is used to prepare AlSi10Mg alloy by laser powder bed melting technology. The seed alloy of the present invention has good refining effect, realizes the refinement of AlSi10Mg alloy grains, significantly improves the strength and plasticity of the alloy, and is conducive to expanding the application of AlSi10Mg alloy in laser powder bed melting technology.
[0021] The seed alloy used in the present invention has low cost, and the method of mixing with AlSi10Mg alloy powder is simple, and it is easy to be applied in the production line without generating harmful pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 In FIG. 1 , A is the microstructure of the AlSi10Mg alloy powder of Example 1, and B is the element content distribution diagram obtained by performing a surface scanning analysis on the microstructure of A.
[0023] Figure 2 This is the X-ray diffraction pattern of the Al-2.63Ti-0.66C-0.13B seed alloy powder of Example 1.
[0024] Figure 3 In the figure, A is the EBSD reconstruction image of the AlSi10Mg alloy of Example 1, and B is the EBSD reconstruction image of the TM-AlSi10Mg alloy of Example 1.
[0025] Figure 4 In the figure, A is the grain size distribution diagram of the AlSi10Mg alloy of Example 1, and B is the grain size distribution diagram of the TM-AlSi10Mg alloy of Example 1.
[0026] Figure 5 In the embodiment, A is the microstructure of the TM-AlSi10Mg alloy of Example 1; B is based on Figure 5 The bright field image of the microstructure of A is obtained by transmission electron scanning analysis, and C is based on Figure 5 Element content distribution diagram obtained by transmission electron scanning analysis of the microstructure of A.
[0027] Figure 6 It is a comparison chart of the mechanical properties of the TM-AlSi10Mg alloy of Example 1 and the AlSi10Mg alloy of Comparative Example 1. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0029] At present, in Al-Si alloys manufactured by laser powder bed melting, optimized solidification paths and refined microstructures are the key to achieving enhanced strength and ductility. However, finding effective nucleating agents to promote significant grain refinement remains a major challenge. Traditionally, nano / submicron-sized ceramic powders (such as TiN, TiCN and LaB6) are usually added to AlSi10Mg alloys, but this method often leads to reduced fluidity of the final powder and agglomeration of ceramic powders, which in turn affects the mechanical properties. Although many researchers have done a lot of exploration to explore and find suitable grain refiners, they all have more or less technical shortcomings such as high cost, change in alloy composition, poor and unstable effect, or contrary to production site technology. Therefore, there is an urgent need to find a way to improve the current mechanical properties of AlSi10Mg and to break the balance of strength-plasticity to a certain extent.
[0030] The present invention provides a method for preparing an AlSi10Mg alloy by laser powder bed melting, which solves the problems existing in the above-mentioned prior art. A new seed powder is introduced into the AlSi10Mg alloy powder to achieve grain refinement, so that the AlSi10Mg alloy prepared by laser powder bed melting has excellent strength and plasticity. The method specifically comprises the following steps:
[0031] The seed alloy powder and the AlSi10Mg alloy powder are uniformly mixed to prepare a mixed powder; the seed alloy powder consists of the following components: 0<Ti≤2.63wt%, 0<C≤0.66wt%, 0<B≤0.13wt%, and the remainder is Al, which is 100% in total; in the mixed powder, the mass fraction of the seed alloy powder is 15wt%.
[0032] The dried mixed powder is spread flat on the base plate of the forming chamber to form an alloy powder layer.
[0033] Under the protection of inert gas, the alloy powder layer was laser scanned and melted layer by layer to obtain AlSi10Mg alloy, which was named TM-AlSi10Mg alloy.
[0034] The present invention introduces seed alloy powder into AlSi10Mg alloy powder for modification to prepare mixed powder, wherein the seed alloy powder is composed of the following components: 0<Ti≤2.63wt%, 0<C≤0.66wt%, 0<B≤0.13wt%, and the remainder is Al, which is 100% in total. Then, the mixed powder is prepared into AlSi10Mg alloy by laser powder bed melting technology. The seed alloy of the present invention has good refining effect, realizes the refinement of AlSi10Mg alloy grains, significantly improves the strength and plasticity of the alloy (yield strength reaches 302±7.6MPa, tensile strength is 479.2±1.5MPa, and elongation is 11.1±0.7%), and is conducive to expanding the application of AlSi10Mg alloy in laser powder bed melting technology. The seed alloy used in the present invention has low cost, and the mixing method with AlSi10Mg alloy powder is simple, easy to be applied in the production line, and no harmful pollutants are generated. The method for preparing the seed crystal of the present invention can be prepared according to the scheme disclosed in CN111996424A.
[0035] The present invention is specifically described below by means of the following examples and comparative examples.
[0036] Example 1
[0037] This embodiment prepares an AlSi10Mg alloy modified by an Al-2.63Ti-0.66C-0.13B seed alloy, which improves the tensile properties of the TM-AlSi10Mg alloy additive and the elongation of the AM-AlSi10Mg alloy additive, so that the aluminum alloy prepared according to the method disclosed in this example can meet the performance requirements in the field of lightweight, high-performance complex parts manufacturing, wherein the Al-2.63Ti-0.66C-0.13B seed alloy means that in the seed alloy, the Ti content is 2.63wt%, the C content is 0.66wt%, the B content is 0.13wt%, and the balance is Al, totaling 100%. The prepared alloy is named TM-AlSi10Mg, and the specific process is:
[0038] (1) Weigh AlSi10Mg alloy powder and Al-2.63Ti-0.66C-0.13B seed alloy powder according to mass percentage. Specifically, AlSi10Mg alloy powder accounts for 85wt% of the total mass, while Al-2.63Ti-0.66C-0.13B seed alloy powder accounts for 15wt%. This precise ratio ensures that the composition of the mixed alloy powder is uniform, which helps to achieve the expected microstructure and mechanical properties. Then, the weighed AlSi10Mg alloy powder and Al-2.63Ti-0.66C-0.13B seed alloy powder are mixed using commercial The shaker mixer fully mixes the AlSi10Mg alloy powder and the Al-2.63Ti-0.66C-0.13B seed alloy powder at a fixed oscillation frequency of 50 Hz for 100 minutes to ensure full contact and uniform dispersion between the powder particles, thereby forming a mixed powder with consistent composition. Next, the mixed powder is placed in a vacuum box at 80°C for 10 hours of drying before the laser powder bed melting process begins.
[0039] (2) Spread the mixed powder on the base plate of the molding chamber to form an alloy powder layer. Under the protection of inert gas (argon) to minimize oxygen contamination and control it below 0.1 vol%.
[0040] (3) The laid alloy powder is laser scanned by EOS M290 equipment to perform layer-by-layer printing and forming. During the forming process, the printing of each layer first completes the entity forming of the internal area by the laser beam according to the preset scanning path. After the internal area is formed, the laser beam scans the external contour from the inside to the outside along the internal entity edge of the layer, and finally completes the printing process of a single layer. This printing step is repeated layer by layer until the additive manufacturing of the TM-AlSi10Mg alloy is completed. The forming process of the above-mentioned printing layers is performed layer by layer, and at the same time, the laser scanning direction of each layer maintains an angle of 67° with the laser scanning direction of the upper layer until the laser additive manufacturing of the alloy is completed.
[0041] In the actual printing process, some preparation work is required:
[0042] First, use 3D modeling software to create a 3D model of the part, and then generate a plane contour model of each layer through slicing software. Next, the scraper transfers the powder from the powder cylinder to the forming chamber, and the laser beam scans and prints according to the model, and finally realizes the stacking and forming of the aluminum alloy parts. In order to ensure the printing effect, alcohol should be used to clean the substrate, powder cylinder, scraper and other parts before the experiment, and argon gas should be filled in the forming chamber. The laser process parameters used for printing the internal solid plane and contour in this embodiment are: the laser power is set to 300W; the laser scanning speed is 1500mm / s; the scanning spacing is 0.1mm; the powder layer thickness is 0.03mm.
[0043] like Figure 1 As shown in Figure A, the AlSi10Mg alloy powder particles are relatively spherical as a whole, with an average particle size of 30 μm. Although some satellite particles and broken powders can be clearly observed, they are considered to be common defects in the powder preparation process and do not affect the fluidity and printing quality during the printing process. Figure 1 As shown in B, by performing element spectrum analysis on the particle, it can be clearly seen that the particle contains three elements: Al, Si and Mg.
[0044] Figure 2 The XRD spectrum of the Al-2.63Ti-0.66C-0.13B seed alloy powder used in this embodiment is shown, indicating that the Al-2.63Ti-0.66C-0.13B seed alloy powder is rich in Ti(C, B) particles (formed by B atoms occupying the C vacancies of TiC crystals), with an average particle size of about 50nm to 300nm. It is worth noting that because the Ti(C, B) phase is formed by B atoms occupying the C vacancies of TiC crystals, Ti(C, B) still retains the structure of TiC crystals. It is completely different from the TiBC ternary phase, which is a ternary phase composed of Ti, B and C.
[0045] Comparative Example 1
[0046] This comparative example prepares a method for preparing an AlSi10Mg alloy without adding seed crystals, and the specific process is as follows:
[0047] First, the AlSi10Mg alloy powder was placed in a vacuum oven at 80° C. for 10 hours for drying, thereby obtaining a dried AlSi10Mg powder.
[0048] Then, the AlSi10Mg powder is spread on the substrate of the molding chamber to form an alloy powder layer. Under the protection of inert gas (argon) to minimize oxygen contamination, controlled below 0.1 vol%.
[0049] Finally, the EOS M290 device is used to laser scan the laid alloy powder for layer-by-layer printing. During the forming process, the printing of each layer first completes the entity forming of the internal area by the laser beam according to the preset scanning path. After the internal area is formed, the laser beam scans the external contour from the inside to the outside along the internal entity edge of the layer, and finally completes the printing process of a single layer. This printing step is repeated layer by layer until the additive manufacturing of the TM-AlSi10Mg alloy is completed. The forming process of the above-mentioned printing layers is performed layer by layer, and the laser scanning direction of each layer is kept at an angle of 67° with the laser scanning direction of the upper layer until the laser additive manufacturing of the alloy is completed.
[0050] In the actual printing process, some preparation work is required. First, use 3D modeling software to create a 3D model of the part, and then use slicing software to generate a plane contour model of each layer. Next, the scraper transfers the powder from the powder cylinder to the forming chamber, and the laser beam scans and prints according to the model, and finally realizes the accumulation and forming of aluminum alloy parts. In order to ensure the printing effect, alcohol should be used to clean the substrate, powder cylinder, scraper and other parts before the experiment, and argon gas should be filled in the forming chamber. The laser process parameters used for printing the internal solid plane and contour in this comparative example are: the laser power is set to 300W; the laser scanning speed is 1500mm / s; the scanning spacing is 0.1mm; the powder layer thickness is 0.03mm.
[0051] Figure 3 Middle A and Figure 3 B in the figure shows the EBSD reconstruction images of the AlSi10Mg alloy additive of comparative example 1 of the present invention and the TM-AlSi10Mg of example 1 of the present invention.
[0052] like Figure 3 As shown in Figure A, the AlSi10Mg alloy additive material of Comparative Example 1 of the present invention exhibits a coarse columnar crystal distribution as a whole. This is a typical microstructure in metal additive manufacturing. This is due to the different cooling rates in the molten pool, and the grains of the AlSi10Mg alloy grow along the epitaxial growth, forming larger columnar crystals and obvious growth textures. Figure 3 As shown in B, the TM-AlSi10Mg of Example 1 of the present invention exhibits an obvious bimodal heterogeneous structure formed by the periodic arrangement of fine equiaxed crystals (melt pool boundary) and coarse equiaxed crystals (inside the melt pool). This is because the faster the cooling rate, the higher the nucleation rate. The Ti (C, B) particles contained in the Al-2.63Ti-0.66C-0.13B seed alloy powder serve as a nucleation substrate, which significantly improves the nucleation rate of α-Al in the aluminum alloy and effectively hinders the growth of columnar crystals inside the melt pool.
[0053] Figure 4 In the figure, A is the AlSi10Mg alloy prepared in comparative example 1, and B is the grain size distribution diagram of TM-AlSi10Mg prepared in example 1, and the average grain size is reduced from 12.5 μm to 2.8 μm. This is because the presence of uniformly dispersed Ti(C, B) particles provides more heterogeneous nucleation sites, improves the nucleation rate of α-Al in the aluminum alloy, promotes the rapid nucleation and growth of grains, and thus reduces the grain size.
[0054] like Figure 5 As shown in Figure A, the marked Ti(C, B) particles are uniformly dispersed in the Al matrix, while the micron-sized eutectic silicon particles show a random distribution. Figure 5Figures B and C show that the nanoscale eutectic silicon particles form a network-like structure radiating inward from the cell boundary, forming a reinforcement phase of a certain thickness, thereby enhancing the hindrance to dislocation movement and helping to slow down the propagation of tensile cracks to a certain extent.
[0055] Experimental example
[0056] Test items: tensile mechanical behavior of the AlSi10Mg alloy specimens in Comparative Example 1 and TM-AlSi10Mg alloy specimens in Example 1.
[0057] Test process: Aluminum alloy standard tensile specimens were prepared according to the preparation methods in Example 1 and Comparative Example 1, and the aluminum alloy specimens of Example 1 and Comparative Example 1 were respectively fixed on a material testing machine (Instron 3382), and tensile tests were performed at room temperature. The tensile test results are shown in Tables 1 and Figure 6 As shown:
[0058] Table 1 Aluminum alloy tensile strength test results
[0059] Group Yield strength(MPa) Tensile strength(MPa) Elongation(%) Comparative Example 1 254±5.8 381±7.3 4.8±1.2 Example 1 302±7.6 479.2±1.5 11.1±0.7%
[0060] From Table 1 and Figure 6 It can be seen that the mechanical properties of the TM-AlSi10Mg alloy additive material prepared by the technical solution provided in this application are greatly improved compared with the AlSi10Mg alloy manufactured by traditional additive manufacturing. Specifically, the yield strength is increased from 254±5.8MPa to 302±7.6MPa, the tensile strength is increased from 381±7.3 to 479.2±1.5, and the elongation is increased from 4.8±1.2% to 11.1±0.7%. It means that the new TM-AlSi10Mg alloy additive material disclosed in the embodiment of the present invention greatly improves the strength and elongation of aluminum alloy parts.
[0061] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.
Claims
1. A laser powder bed melting method for preparing AlSi10Mg alloy, characterized in that: The following steps are involved: The seed alloy powder and the AlSi10Mg alloy powder are uniformly mixed to prepare a mixed powder; the seed alloy powder is composed of the following elements: 0<Ti≤2.63wt%, 0<C≤0.66wt%, 0<B≤0.13wt%, and the remainder is Al, which is 100% in total; in the mixed powder, the mass fraction of the seed alloy powder is 15wt%; Spreading the dried mixed powder on a base plate of a forming chamber to form an alloy powder layer; Under the protection of inert gas, the alloy powder layer is laser scanned and melted layer by layer to obtain AlSi10Mg alloy.
2. The laser powder bed melting method for preparing AlSi10Mg alloy according to claim 1, characterized in that: The average particle size of the seed alloy powder is 9.62 μm. The seed alloy powder contains Ti(C, B) particles. The Ti(C, B) particles are formed when B atoms occupy C vacancies in TiC crystals. The particle size of the Ti(C, B) particles is 50 nm to 300 nm.
3. The laser powder bed melting preparation method of AlSi10Mg alloy according to claim 1, characterized in that: The average particle size of the AlSi10Mg alloy powder is 30 μm.
4. The laser powder bed melting method for preparing AlSi10Mg alloy according to claim 1, characterized in that: During the forming process, the printing of each layer is first completed by the laser beam according to a preset scanning path to complete the solid forming of the internal area. After the solid forming of the internal area is completed, the laser beam scans and forms the external contour from the inside to the outside along the internal solid edge of the layer, and finally completes the single-layer printing; the steps of single-layer printing are repeated layer by layer until the additive manufacturing of AlSi10Mg alloy is completed.
5. The laser powder bed melting method for preparing AlSi10Mg alloy according to claim 4, characterized in that: During the forming process, the laser scanning path of each layer forms an angle of 67° with the laser scanning path of the previous layer.
6. The laser powder bed melting method for preparing AlSi10Mg alloy according to claim 4, characterized in that: The laser process parameters used for printing internal entities and contours are: the laser power is set to 200W~350W, the laser scanning speed is 600mm / s~1800mm / s, the scanning spacing is 0.1mm, and the powder layer thickness is 0.03mm.
7. The laser powder bed melting method for preparing AlSi10Mg alloy according to claim 1, characterized in that: The composition of the AlSi10Mg alloy powder is: 0<Si≤9.8wt%, 0<Mg≤0.6wt%, and the content of Al is ≥89.6wt%, which is 100% in total.
8. AlSi10Mg alloy prepared according to the preparation method according to any one of claims 1 to 7.
9. The AlSi10Mg alloy according to claim 8, characterized in that: The average grain size of the AlSi10Mg alloy is 2.8 μm.
Citation Information
Patent Citations
TiCB-Al seed crystal alloy, manufacturing method thereof and heritable aluminum alloy
CN111996424A
Aluminum alloy powder, preparation method and application of aluminum alloy powder in laser additive manufacturing
CN112570706A
High-performance two-phase hybrid reinforced aluminum-based composite material and preparation method thereof
CN114350998A
Special high-strength aluminum alloy for SLM and SLM forming method therefor
WO2023168874A1
Cited By
Method for improving surface hardness of AlSi10Mg alloy based on fractional cold rolling
CN120772550A
ReB6 reinforced AlSi10Mg alloy composite material and preparation method thereof
CN120940666A